Distribution of volatile organic compounds by distance from industrial complexes and potential health impact on the residents. - Kim, A Ram; Bang, Jin-Hee; Lee, Sunghee; Sim, Chang Sun; Kim, Yangho; Lee, Jiho (International Journal of Environmental Health Research, 2024)
Volatile organic compounds (VOCs) are the air pollutants emitted from the petrochemical industry known to pose adverse health effects on workers. The database based on the third phase of The Environmental Health Study in the Korean National Industrial Complexes (EHSNIC) in Ulsan conducted from 2018 to 2021 was used. Subjects were divided into the exposed and control group according to the estimated pollution level and distances from the industrial complexes. Ambient benzene, ethylbenzene, and xylene were significantly higher in the exposed group compared to the controls, as well as their metabolites. Risk of chronic disease and atopic dermatitis was higher in the exposed group which was supported by higher serum inflammatory markers and high hazard index of the exposed region. These results can draw attention to people engaged with environmental plans and used as primary data when making policies to reduce pollutant levels around industrial complexes.